Estrategias de promoción y su relación con el posicionamiento de marca de las empresas turísticas de la ciudad de Iquitos, 2019 - Reyna Guzmán, Sofía (2020)
In the present investigation called: 'Strategies of promotion and its relation with the positioning of brand of the tourist companies of the city of Iquitos, year 2019', has as purpose to determine the relation between the variables of the tourist companies, by which opted for an applied type of correlational level research with a non-experimental design, in which 413 clients were taken as a population. When the formula was applied, a sample of 199 clients was obtained and applied as a data collection technique. survey with a questionnaire of questions as an instrument; finally reaching the following conclusions: After analyzing the results it was determined that the promotion strategies developed by the company Amazon Explorer SRL, is adequate, however the companies Jungle Man Expeditions E.I.R.L (54%), Amazon King S.A.C. (61%) and Paucar Tours E.I.R.L. (44%), develop inadequate promotion strategies, for their part the company Otorongo Expeditions E.I.R.L. and La Fuente del Amazonas E.I.R.L. They have achieved a regular result. After analyzing the results, it was determined that the positioning achieved by the companies in the market is not favorable for their growth, since the majority only achieved a regular (medium) positioning, due to the deficient development of strategies, in terms of criteria Desirability, the main shortcomings is the similarity with others mark, companies do not care about providing a service with characteristics different from the competition, the same happens with the criterion of compliance, because the services they offer are not related to the characteristics of the brand. Finally, it is determined that there is a significant relationship between the promotion strategies and the brand positioning of the tourism companies of the city of Iquitos, year 2019, which is corroborated by the statistician Rho de Spearman through a correlation coefficient of 0,853, which, being high, accepted the research hypothesis.